2009
DOI: 10.1371/journal.pntd.0000478
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discovery for Schistosomiasis: Hit and Lead Compounds Identified in a Library of Known Drugs by Medium-Throughput Phenotypic Screening

Abstract: BackgroundPraziquantel (PZQ) is the only widely available drug to treat schistosomiasis. Given the potential for drug resistance, it is prudent to search for novel therapeutics. Identification of anti-schistosomal chemicals has traditionally relied on phenotypic (whole organism) screening with adult worms in vitro and/or animal models of disease—tools that limit automation and throughput with modern microtiter plate-formatted compound libraries.MethodsA partially automated, three-component phenotypic screen wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
304
4
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(321 citation statements)
references
References 45 publications
8
304
4
3
Order By: Relevance
“…To my knowledge, the life cycle of S. haematobium is currently maintained only in two laboratories, namely the Theodor Bilharz Research Institute (Giza, Egypt) and the Schistosomiasis Resource Center. ' Sibling ' species of S. haematobium, such as S. bovis, S. matthei or S. margrebowiei, the life cycles of which can be maintained in laboratory rodents, might serve as models for S. haematobium (Agnew et al 1989).…”
Section: S C H I S T O S O M a M A N S O N Imentioning
confidence: 99%
See 1 more Smart Citation
“…To my knowledge, the life cycle of S. haematobium is currently maintained only in two laboratories, namely the Theodor Bilharz Research Institute (Giza, Egypt) and the Schistosomiasis Resource Center. ' Sibling ' species of S. haematobium, such as S. bovis, S. matthei or S. margrebowiei, the life cycles of which can be maintained in laboratory rodents, might serve as models for S. haematobium (Agnew et al 1989).…”
Section: S C H I S T O S O M a M A N S O N Imentioning
confidence: 99%
“…Schistosomula are incubated in Basch medium (Basch, 1981) supplemented with serum and antibiotics or other culture media (Smyth and Halton, 1983). Our own studies have shown that schistosomula survive for at least 96 h in different media (Basch,MEM,DMEM or TC 199) reported that schistosomula survive in Basch medium for several weeks (Abdulla et al 2009). In Fig.…”
Section: S Mansoni In Vitro Assay Based On Schistosomulamentioning
confidence: 99%
“…Screens were performed at 5 μM and 10 µM against schistosomula and adults, respectively, over the course of 3 days. A previous constrained nomenclature is used to record phenotypes [16] (every 24 h) that describe both motion and morphological changes. For schistosomula, the terms employed are 'dead' (D), 'degenerate' (Deg), 'round' (R), 'overactive' (O) and 'dark' (Dark).…”
Section: Resultsmentioning
confidence: 99%
“…Maintenance of the S. mansoni life cycle, preparation of schistosomula and adult worms, compound storage and treatment of schistosomula and adult worms were as described [16]. Compounds were dissolved in DMSO.…”
Section: Schistosoma Screens and Temmentioning
confidence: 99%
“…Maintenance of the S. mansoni life cycle, preparation of somules and adult worms, compound storage, and treatment of somules and adult worms were as described (Abdulla et al, 2009;Colley, Wikel, 1974;Duvall, DeWitt, 1967). Somules were cultured for four days in the presence of compounds at three concentrations, 0.1, 1.0 and 10 µM.…”
Section: In Vitro Screening Of S Mansoni Somules and Adult Wormsmentioning
confidence: 99%